Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, fall 1986 - Proescholdt, Market al (1986)
List of birds and locations contributed by Mark Proescholdt with observers Beth Proescholdt, B.J. Rose, Babs Padelford, Loren Padelford and others. Field notes include sighting of an Albino Barred Owl in Hardin County. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed